Kesiapan Guru Sekolah Dasar Menghadapi Tantangan Disrupsi Teknologi dalam Pembelajaran Kurikulum Merdeka (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study examines the preparedness of elementary school teachers in Indonesia to navigate the digital age and implement the Merdeka Curriculum. Findings reveal significant challenges in digital literacy, adequate teacher training, and sufficient school infrastructure. While student interest in technology is high, teachers struggle to effectively integrate technology into teaching and manage dynamic classrooms. The research underscores the urgent need for enhanced digital competency development among teachers, improved access to technology, and the development of teaching strategies responsive to technological advancements and the needs of 21st-century learners.